Respuesta :

Answer:

[tex]\frac{1}{3}[/tex]

Step-by-step explanation:

[tex]\frac{5}{6} -x=\frac{1}{2}[/tex]

Add x to both sides.

[tex]\frac{5}{6} -x+x=\frac{1}{2} +x[/tex]

[tex]\frac{5}{6} =\frac{1}{2} +x[/tex]

Subtract 1/2 from both sides.

[tex]\frac{5}{6} -\frac{1}{2} =\frac{1}{2} - \frac{1}{2} +x[/tex]

[tex]\frac{5}{6} -\frac{1}{2} = x[/tex]

Find a common denominator to subtract the fractions. The least common multiple of 6 and 2 is 6. Adjust 1/2 to a fraction with 6 in the denominator.

[tex]\frac{1}{2}*\frac{3}{3} =\frac{3}{6}[/tex]

Now you can subtract:

[tex]\frac{5}{6} -\frac{3}{6} = x=\frac{2}{6}[/tex]

Simplify.

[tex]\frac{1}{3}[/tex]

[tex]\dfrac{5}{6}[/tex] minus [tex]\dfrac{1}{3}[/tex] is equal to [tex]\dfrac{1}{2}[/tex].

Given:

[tex]\dfrac{5}{6}[/tex] minus an unknown number is equal to [tex]\dfrac{1}{2}[/tex].

To find:

The unknown number.

Explanation:

Let [tex]x[/tex] be the unknown number. Then

[tex]\dfrac{5}{6}-x=\dfrac{1}{2}[/tex]

Isolate the variable [tex]x[/tex].

[tex]-x=\dfrac{1}{2}-\dfrac{5}{6}[/tex]

[tex]-x=\dfrac{3-5}{6}[/tex]

[tex]-x=\dfrac{-2}{6}[/tex]

[tex]-x=-\dfrac{1}{3}[/tex]

[tex]x=\dfrac{1}{3}[/tex]

Therefore, the unknown number is [tex]\dfrac{1}{3}[/tex].

Learn more:

https://brainly.com/question/899233

ACCESS MORE
EDU ACCESS
Universidad de Mexico